Upper bound of second Hankel Determinant for subclasses of close-to-convex functions / Muhammad Fazrul Azmi - Azmi, Muhammad Fazrul (Universiti Teknologi MARA, Negeri Sembilan, 2024)
An analytic function assumes that every complex number, with possibly by one exception, infinitely often in any neighborhood of an essential singularity. That is an example of complex analysis from Picard’s great theorem. An analytic function, A, is one-to-one mapping of one region onto another region in the complex plane. The normalized analytic function is defined if function is regular and univalent in A (Goodman, 1983).